Middle Class Pentecostalism in Argentina Inappropriate Spirits - Koehrsen, Jens (Religion in the Americas, 2016)
Middle-Class Pentecostalism in Argentina: Inappropriate Spirits offers an intriguing account of how the middle class relates to Latin America´s most vibrant religious movement. The study posits that middle class Pentecostalism forges a milder, more socially acceptable form of the movement. Readership: All interested in religion in Latin-America, social class and religion, Pentecostalism and anyone concerned with sociology of religion and religious studies.